EFFECTIVENESS OF CHANGES TO LAW NUMBER 1 OF 1974 TO LAW NO 16 OF 2019 CONCERNING EARLY MARRIAGE (Case Study in Hamparan Perak District) - Aziz, Tanzilul; Mukhsin, Abd. (Academy of Education Journal, 2023)
This article aims to analyze the effectiveness of Law no. 16 of 2019 in reducing the rate of early marriage. Indonesia is a country whose population is relatively large in early marriage. Early marriage is legal if the terms and conditions are met. Ironically, in line with the rise in early marriage, the divorce rate has actually increased. Furthermore, divorce plaintiffs are teenagers who initially married at an early age. The urgency of this research is to review the effectiveness of the law in reducing the number of early marriages in Hamparan Perak District. This article uses a qualitative method with a normative juridical approach. The data collection techniques used were interviews, observation and documentation. The primary data source in this research is the results obtained through interviews and observation, while the secondary data used is a literature review. The results of the research show that in Hamparan Perak District, changes to this law were effective because they were able to reduce the number of early marriages. However, the author still found several young couples who chose to get married. This problem can be suppressed through strict regulations and requirements. The change in the law regarding the age of marriage is very effective in reducing the number of early marriages in Hamparan Perak District